Analysis of Farmers' Risk Preference Factors on the Determination of Rice Micro Insurance Premiums Using the Utility Theory - Pramudhita, Annisa; Riaman, Riaman; Pryimak, Evgen (Operations Research: International Conference Series, 2023)
Business activities in the agricultural sector, especially rice farming, will always be faced with a high risk of uncertainty. The risks experienced by farmers come from the natural environment, natural disasters, climate, and plant-disturbing organisms. To avoid this situation, the government is currently providing the best solution in the form of a Rice Farming Insurance program (AUTP), which is expected to provide protection against the risk of crop failure that farmers may experience. The purpose of this research is to analyze rice farmers' risk preferences in determining rice farming insurance premiums. The research method for rice farmers' risk preferences was analyzed using constant relative risk averse (CRRA) utility theory. Based on the research results, rice farmers in Majalaya District, Bandung Regency has a very risk averse risk preference. The risk preferences of farmers participating in AUTP and non-AUTP are very risk averse. The policy implications that can be explained based on the results of this study are increasing farmers' understanding regarding the description and benefits of agricultural insurance through counseling and assistance by the Agriculture Service and PT. Jasindo, so that rice farmers in Majalaya District, Bandung Regency have awareness of the benefits of insurance. Encouraging the participation of rice farmers in Majalaya District in the AUTP program can also be carried out by prioritizing rice farmers with very risk averse risk preferences. The policy implications that can be explained based on the results of this study are increasing farmers' understanding regarding the description and benefits of agricultural insurance through counseling and assistance by the Agriculture Service and PT. Jasindo, so that rice farmers in Majalaya District, Bandung Regency have awareness of the benefits of insurance. Encouraging the participation of rice farmers in Majalaya District in the AUTP program can also be carried out by prioritizing rice farmers with very risk averse risk preferences. The policy implications that can be explained based on the results of this study are increasing farmers' understanding regarding the description and benefits of agricultural insurance through counseling and assistance by the Agriculture Service and PT. Jasindo, so that rice farmers in Majalaya District, Bandung Regency have awareness of the benefits of insurance. Encouraging the participation of rice farmers in Majalaya District in the AUTP program can also be carried out by prioritizing rice farmers with very risk averse risk preferences.